DNA content variation and its significance in the evolution of the genus Micrasterias (Desmidiales, Streptophyta) - Poulíčková, Aloisie; Mazalová, Petra; Vašut, Radim J; Šarhanová, Petra; Neustupa, Jiří; Škaloud, Pavel (PloS one, 2014)
It is now clear that whole genome duplications have occurred in all eukaryotic evolutionary lineages, and that the vast majority of flowering plants have experienced polyploidisation in their evolutionary history. However, study of genome size variation in microalgae lags behind that of higher plants and seaweeds. In this study, we have addressed the question whether microalgal phylogeny is associated with DNA content variation in order to evaluate the evolutionary significance of polyploidy in the model genus Micrasterias. We applied flow-cytometric techniques of DNA quantification to microalgae and mapped the estimated DNA content along the phylogenetic tree. Correlations between DNA content and cell morphometric parameters were also tested using geometric morphometrics. In total, DNA content was successfully determined for 34 strains of the genus Micrasterias. The estimated absolute 2C nuclear DNA amount ranged from 2.1 to 64.7 pg; intraspecific variation being 17.4-30.7 pg in M. truncata and 32.0-64.7 pg in M. rotata. There were significant differences between DNA contents of related species. We found strong correlation between the absolute nuclear DNA content and chromosome numbers and significant positive correlation between the DNA content and both cell size and number of terminal lobes. Moreover, the results showed the importance of cell/life cycle studies for interpretation of DNA content measurements in microalgae.
Keywords: Microalgae; Genome Size; Phylogeny; DNA rostlinná; Biological Evolution; DNA, Plant; Streptophyta; délka genomu; biologická evoluce; genom rostlinný; Micrasterias; variabilita počtu kopií segmentů DNA; mikrořasy; DNA Copy Number Variations; Genome, Plant; fylogeneze; chromozomy rostlin; Chromosomes, Plant